From "blue sky" to real world research. Issue 3 (1st August 2018) - Ryan, Irene
Abstract : Purpose: The purpose of this paper is to share reflective insights on three key questions of concern to critical diversity scholars: what influences play a part in framing a research project and the research questions, what determines the chosen methodology and what knowledge contributions do we want our research to make? Design/methodology/approach: The paper, drawing on organisational ethnography, incorporates key fieldwork experiences to provide reflective insights on an innovative research project design conducted in multiple organisation sites. Findings: The paper highlights the author's learning from the conceptualisation of an innovative research project to the actual "doing" of what was proposed. It reflects on the unforeseen dilemmas that required continual adaptations be made because of the shifting demands of the research settings. Practical implications: The paper is important as it provides the sharing of ideas into the influences that shaped a major piece of externally funded research and highlights a range of practical considerations if planning a critical diversity research project where negotiating access to organisations is required. Originality/value: By reflecting on some important learning and insights into the crafting of an innovative research project and the challenges of enacting what was proposed, the paper is of value to post-doctoral and early career scholars and/or researchers interested in some insights into operationalising an organisational ethnographic methodology.